Propuesta para el manejo sostenible del turismo - Zeballos Gando, María M. (2010)
This article analyzes the humpback whale watching activity in the area of Salinas. It examines the history, current situation and supporting industry. With this basis, we proceed to identify key actors and issues, after which it performs a SWOT analysis and impact analysis of regulations. After which ends with an agreement of partnership, recommendations for regulation, and a list of good